Pentraxin 3 in bronchoalveolar lavage fluid and plasma in non-neutropenic patients with pulmonary aspergillosis. (April 2019) - Li, H.; Liu, L.; Zhou, W.; Rui, Y.; He, B.; Shi, Y.; Su, X.
Abstract: Objectives: Pentraxin 3 (PTX3) contributes to resistance to Aspergillus infections. This study aimed to evaluate the presence of PTX3 in bronchoalveolar lavage fluid (BALF) and plasma in non-neutropenic patients with pulmonary aspergillosis. Methods: BALF ( n = 211) and plasma samples ( n = 307) were collected from patients initially suspected of having pulmonary aspergillosis. Among these, 112 cases (51 BALF samples and 89 plasma samples) were proven to be pulmonary aspergillosis. These cases were classified as invasive pulmonary aspergillosis (IPA), subacute invasive aspergillosis (SAIA) and chronic pulmonary aspergillosis (CPA). The remaining cases were non-aspergillosis controls and were diagnosed with community-acquired pneumonia (CAP), lung cancer and pulmonary cryptococcosis. Plasma samples from healthy controls ( n = 30) were also collected. Results: The median (interquartile range, IQR) BALF PTX3 for aspergillosis cases was significantly higher than for non-aspergillosis cases: 6.97 (2.91–13.51) ng/mL versus 1.26 (0.76–1.76) ng/mL. When the PTX3 threshold was set at 1.9 ng/mL, sensitivity and specificity of BALF PTX3 for aspergillosis were 86.3% (95%CI 83.8–88.4%) and 82.5% (95%CI 79.7–85.0%), respectively. The median (IQR) plasma PTX3 for aspergillosis cases was significantly higher than for non-aspergillosis cases and healthy controls: 7.10 (3.36–9.53) ng/mL versus 1.57 (0.86–2.35) ng/mL versus 1.10 (0.49–1.51) ng/mL. With a PTX3 threshold of 2.3 ng/mL, sensitivity and specificity were 79.8% (95%CI 70.1–81.2%) and 72.1% (95%CI 69.5–74.5%) respectively. Conclusions: BALF and plasma PTX3 may be biomarkers for differentiating aspergillosis from other conditions such as CAP, lung cancer, and pulmonary cryptococcosis in non-neutropenic patients.